2015
DOI: 10.1517/17425247.2015.1018175
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric nanoparticle drug delivery technologies for oral delivery applications

Abstract: Introduction Many therapeutics are limited to parenteral administration. Oral administration is a desirable alternative because of the convenience and increased compliance by patients, especially for chronic diseases that require frequent administration. Polymeric nanoparticles are one technology being developed to enable clinically feasible oral delivery. Areas covered This review discusses the challenges associated with oral delivery. Strategies used to overcome gastrointestinal barriers using polymeric na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(140 citation statements)
references
References 131 publications
(138 reference statements)
2
128
0
2
Order By: Relevance
“…Studies in dogs have evaluated use of BMP in bone defects revealed complete healing of mandibular defects within three months and significant improvement was observed in degree of mineralization, bone thickness and biomechanical strength [346]. A great deal of resources has been invested in the area of micro and nanoparticles in search of simple, efficient and affordable drug delivery systems [347,348,349,350]. Researchers have also tested microspheres and nanoparticles for delivery of BMPs, cytokines and mesenchymal cells [351,352,353,354].…”
Section: Developments and The Future Of Bone Augmentationmentioning
confidence: 99%
“…Studies in dogs have evaluated use of BMP in bone defects revealed complete healing of mandibular defects within three months and significant improvement was observed in degree of mineralization, bone thickness and biomechanical strength [346]. A great deal of resources has been invested in the area of micro and nanoparticles in search of simple, efficient and affordable drug delivery systems [347,348,349,350]. Researchers have also tested microspheres and nanoparticles for delivery of BMPs, cytokines and mesenchymal cells [351,352,353,354].…”
Section: Developments and The Future Of Bone Augmentationmentioning
confidence: 99%
“…Oral drug delivery is the most widely used and most readily accepted form of drug administration as it is simple, painless and selfadministered [36,37]. It is the most convenient and safe administration route, particularly for chronic delivery, but it poses a number of challenges for the formulator in terms of bioavailability (fraction of drug actually reaching the circulation) due to degradation by enzymes and harsh pH conditions, low solubility of some drugs or limited absorption by the GIT epithelium [38].…”
Section: Challenges Of In Vivo Researchmentioning
confidence: 99%
“…Nanotechnology-based novel drug delivery approaches address issues associated with the current pharmaceutical approach by enhancing shelf-life and acceptability either by uptake efficacy or patient compliance [9–11]. Nanoparticles can be delivered by various entry routes, including oral administration [12, 13], vaccination [14] and aerosol-based drug delivery [15–17], depending on the therapeutic requirement. The selection of the drug administration approach is based principally on the target localization, drug retention time, physiological barriers and pathobiology of the target disease [18].…”
Section: Nanoparticles Of Biomedical Importancementioning
confidence: 99%